Prenatal risk factors for urgent atrial septostomy at birth in fetuses with transposition of the great arteries: a systematic review and meta-analysis. (1st February 2022) - Buca, Danilo; Winberg, Per; Rizzo, Giuseppe; Khalil, Asma; Liberati, Marco; Makatsariya, Alexander; Greco, Francesca; Nappi, Luigi; Acharya, Ganesh; D'Antonio, Francesco
Abstract: Purpose of the article. To explore the role of fetal echocardiography in predicting the risk of urgent balloon atrial septostomy (BAS) at birth in fetuses diagnosed with transposition of the great arteries (TGA). Material and methods: Medline, Embase, and Cochrane databases were searched. The primary aim was to explore the differences in prenatal echocardiographic parameters among fetuses diagnosed with TGA that required urgent BAS within 24 h of birth due to life-threatening cyanosis compared to those who did not require such procedure. Random-effect meta-analyses were used to compute the data. Results: Six studies (292 fetuses) were included. Restrictive appearance of the FO was present in 64.5% (95% CI = 39.8–85.7) of fetuses with TGA requiring BAS at birth compared to 7.9% (95% CI = 2.1–16.8) not requiring such procedure (OR = 71.1; 95% CI = 8.3–608.5, p  < .0001). Hypermobile appearance of the atrial septum was present in 39.1% (95% CI = 26.4–56.5) of fetuses requiring BAS at birth compared to 9.8% (95% CI = 1.4–24.3) of those which did (OR 3.6; 95% CI = 1.4–9.0, p  = .05). There was no difference in the prevalence of redundant ( p  = .374) or fixed ( p  = .051) atrial septum, bidirectional flow in the DA ( p  = .26) or an abnormal size of the DA ( p  = .06) in fetuses requiring urgent BAS at birth compared to those which did not. Mean (±SD) size of the right atrium was smaller in the fetuses with TGA undergoing urgent BAS at birth (23.4 ± 6.7) compared to those which did not (29.2 ± 6.2, p  = .01). The mean (±SD) ratio between the FO and the aortic valve diameters (1.01 ± 0.41 versus 1.41 ± 0.43, p  = .009) and the mean (±SD) ratio between the FO diameter and the septal length (0.36 ± 0.13 versus 0.51 ± 0.14, p  = .001) were significantly smaller in fetuses requiring compared to those not undergoing urgent BAS at birth. The diagnostic accuracy of each independent ultrasound marker of the need for urgent BAS showed an overall good specificity but a low sensitivity. Conclusion: Fetal echocardiography prior to birth can stratify the risk of BAS in fetuses with TGA. Further studies are needed to validate these findings and build individualized multiparametric predictive models in order to more accurately identify those fetuses with TGA at a higher risk of urgent BAS after birth.